PENGARUH CORPORATE SOCIAL RESPONSIBILITY, INTENSITAS MODAL, DAN PERSAINGAN TERHADAP AGRESIVITAS PAJAK PERUSAHAAN - AWALINA MAULIDAH, HIDAYATUL; PRASTIWI, DEWI (Jurnal Akuntansi AKUNESA, 2019)
This study aims to examine the effect of Corporate Social Responsibility (CSR), Capital Intensity, and Competition Intensity on Tax Aggressiveness. The sample used is manufacturing companies listed on the BEI in the 2014-2017 period. Based on the purposive sampling method, there are 29 companies that become the study sample. Multiple linear regression analysis with SPSS 23 program was used to analyze the data of this study. The results showed that CSR had no effect on tax aggressiveness. Capital intensity has a negative effect on tax aggressiveness, while competition intensity has a positive effect on tax aggressiveness. Keywords: CSR; Capital Intensity; Competition; Tax Agressiveness.